Disasters : natural and man-made catastrophes through the centuries - Guiberson, Brenda Z. (New York : Henry Holt and Co., 2010)
"Natural and man-made disasters have the power to destroy thousands of lives very quickly. Both as they unfold and in the aftermath, these forces of nature astonish the rest of the world with their incredible devastation and magnitude. In this collection of ten well-known catastrophes ... Brenda Guiberson explores the causes and effects, as well as the local and global reverberations of these calamitous events."--barnesandnoble.com
"Christy Ottaviano Books."
Keywords: Natural disasters; Disasters; Juvenile Literature